ANALISIS SISTEM ANTRIAN MODEL MULTI PHASE-MULTI CHANNEL PADA SENTRA PELAYANAN KIOS 3 IN 1 BBPLK SEMARANG - Ujiati Suci Rahayu; Rochdi Wasono; Tiani Wahyu Utami (Universitas Muhammadiyah Semarang, 2017)
The queue process is a process associated with the arrival of a customer at a service facility, then waited in a row (queue) when all services are busy, andleaving the place after getting the service. The queue process can happenanywhere, including in BBPLK Semarang. A wide variety of services such asregistration, competency testing, placement, making the rights of participantsand certificates. Therefore, it is necessary to study on the queuing system tooptimize service to customers. The purpose of this study was to determine thestatistical analysis deskriptive, making modeling a queue that services moreeffectively and efficiently and interpret the queuing models. The research in thispaper begins with a queuing system design kiosk 3 in 1 BBPLK Semarang.Then, the retrieval of data for each counter in the form of many arrivals anddepartures every 15 minutes. The collected data is then tested to determinewhether the data is distributed Poisson or not. Once known Poisson distributeddata, followed by determining a model queue at each phase and determine therate of arrivals and departures every service counter. The next step is to analyzethe size of the performance of each phase in the form of the average number ofcustomers in the system, the average number of customers in the queue, theaverage length of customer in the system, and the average length of customer inthe queue. Keywords : queue, model multi phase-multi channel, poisson, eksponensial